Promiscuous Interactions of gp78 E3 ligase CUE domain with polyubiquitin chains - Liu, Shan (2012)
Recognition of ubiquitin and polyubiquitin chains by ubiquitin-binding domains (UBDs) is vital for ubiquitin-mediated signaling pathways. The endoplasmic reticulum resident RING finger ubiquitin ligase (E3) gp78 regulates critical proteins via the ubiquitin-proteasome system to maintain cellular homeostasis and includes a UBD known as the CUE domain, which is essential for function. A probable role of this domain is to recognize ubiquitin modified substrates, enabling gp78 to assemble polyubiquitin chains on these substrates and mark them for degradation. Here, we report the molecular details of the interaction of gp78CUE domain with ubiquitin and diubiquitin. The gp78CUE domain exhibits a well-defined set of interactions with ubiquitin and a dynamic, promiscuous interaction with diubiquitin chains. This leads to a model where the CUE domain functions to both facilitate substrate binding and enables switching between adjacent ubiquitin molecules of a growing chain to facilitate processivity in ubiquitination.